CURSOS SUPERIORES DE TECNOLOGIA EM SEGURANÇA NO TRABALHO: PERCEPÇÃO DO(A)S ALUNO(A)S E PROFESSORE(A)S - Santos, Wellington Luiz (2015)
The dissertation analyzes the technological education in its current configuration, investigating the perception of students of a degree of security technology at work, for their insertion in the professional field; investigating the hypothesis that these agents can sense lags in the real social process, which are expressed in the inadequacy between: the course structure of security technology at work, the judicial-legal sphere and the structure of the labor market. The research adopts an exploratory qualitative approach, based on the case study method to collect data. To discuss the issue of the professional formation and technological education in Brazil, we use bibliographic research in order to unveil the type teaching evolution in the contextual way in its relation to economic phenomena, social and political. To verify the research hypothesis, we investigated students and teachers of a safety course at work in an educational institution, through questionnaires and interviews; and we conducted a documentary research in related legislation on the issues of professional regulations in the specific field of the safety area at work. The results confirmed the research hypothesis, establishing serious modifications in the purpose and objectives of technological training, especially in its social effects. The documentary research articulated to the subjects’ answers, indicated the gap of the politics between the education area and the politics of labor and employment. Nevertheless, in the teachers’s discurses evidences were found to support hypothesis of the issue dealt with here, extend to other courses. The results show that it are necessary, further studies on this issue and to restablish a research agenda aimed at agents and process involved in this context, for the purpose of promoting discussions and identify actions and procedures to guide, correct any distortions and reduce the possibility of the repetition of events related to the problem under discussion.